Heterogeneous Innovations and Growth Under Imperfect Technology Spillovers - Karam Jo; Seula Kim (Institute of Labor Economics (IZA), 2024)
We study how frictions in learning others' technology, termed "imperfect technology spillovers," impact firm innovation strategies and the aggregate economy through changes in innovation composition. We develop an endogenous growth model that generates strategic innovation decisions, where multi-product firms improve their products via own-innovation and enter new product markets through creative destruction under learning frictions. In our model, firms with technological advantages intensify own-innovation as learning frictions enable them to protect their markets from competitors, thereby reducing creative destruction of rivals. This pattern gets more pronounced when competitive pressure increases exogenously. Using U.S. administrative firm-level data, we provide regression results supporting the model predictions.
Keywords: L11; L25; O31; O33; O41; 330; innovation; technology spillover; endogenous growth; competition